“It’s Just Flourishing Hope Everywhere”: The Experiences of Incarcerated Men Sharing Their Stories - Tryon, Rebecca (International journal of offender therapy and comparative criminology, 2023)
Of the 2.2 million people incarcerated throughout the United States, 93% are men. The current phenomenological study adds to the existing body of qualitative research on the lived experiences of men who are incarcerated and supports storytelling as a therapeutic technique. Four essential themes were revealed through an analysis of participant interviews: (1) substance use, (2) anticipation of storytelling, (3) the act of storytelling, and (4) reflections on storytelling. Understanding these experiences can assist in the development of storytelling-based interventions and community programing that is mutually beneficial to both the teller and the listener.